Bibliometric review on human resources management and big data analytics - Fauzi, Muhammad Ashraf; Kamaruzzaman, Zetty Ain; Abdul Rahman, Hamirahanim (Emerald Publishing, 2022)
Purpose; This study aims to provide an in-depth understanding of big data analytics (BDA) in human resource management (HRM). The emergence of digital technology and the availability of large volume, high velocity and a great variety of data has forced the HRM to adopt the BDA in managing the workforce. Design/methodology/approach; This paper evaluates the past, present and future trends of HRM through the bibliometric analysis of citation, co-citation and co-word analysis. Findings; Findings from the analysis present significant research clusters that imply the knowledge structure and mapping of research streams in HRM. Challenges in BDA application and firm performances appear in all three bibliometric analyses, indicating this subject’s past, current and future trends in HRM. Practical implications; Implications on the HRM landscape include fostering a data-driven culture in the workplace to reap the potential benefits of BDA. Firms must strategically adapt BDA as a change management initiative to transform the traditional way of managing the workforce toward adapting BDA as analytical tool in HRM decision-making. Originality/value; This study presents past, present and future trends in BDA knowledge structure in human resources management.